Exploring innovative and creative ways of teaching - Carmen Franco Vázquez; Carol Gillanders (Multidisciplinary Journal for Education, Social and Technological Sciences)
With the intention of providing a starting point to reflect on both aspects in which the subject Teaching Innovation and Introduction to Educational Research in Arts of the master’s degree in Teaching in Secondary School breaks up and merges, we created a situation, understood as a learning environment, that seeks to show us how we react before a situation different from the expected one. For this reason, we played with the idea of something in construction, something that is still wrapped up in white paper: tables badly placed, chairs on tables, papers covering chairs and tables, or parts of the classroom... And in this setting some videos were projected that talked about classrooms, of the present and the past, of diverse artistic experiences. Confusion, surprise, but slowly a discussion starts. And from the reflections raised, the exchange of opinions and relating the assignment to other subjects of the master’s degree, in particular with Learning and Teaching of Art, we began to go more deeply into the meaning of various concepts related to teaching and research by means of projects carried out in groups and from different approaches. The purpose was to offer a space to experience through action, to get to know our previous ideas and how to approach the different research paradigms.